Penerapan Asas Transparansi dalam mengelola dana Zakat (Studi pada Baitul Mal Aceh) - Mursalmina (LPPM STEBIS YPII, 2025)
This research aims to determine how the principle of transparency is implemented by Baitul Mal Aceh in managing zakat funds. The study uses a qualitative method with data collected through interviews with nine informants directly related to the research: (i) Baitul Mal Aceh officials, (ii) Muzakki (zakat givers), and (iii) Mustahik (zakat recipients). The findings show that Baitul Mal Aceh has made efforts to apply transparency principles in managing zakat funds based on the following indicators: easily accessible information, a website and other publication media, media publications of activities and financial reports, regular reports accessible to the public, and the availability of annual reports. However, some challenges were identified, such as a lack of digital literacy among some of the Muzakki and Mustahik regarding the digital information provided by Baitul Mal. Despite this, their trust in the Baitul Mal Aceh institution remains unaffected